Resilience Quotient : RQ - Sucaromana, Ashara (วารสารสันติศึกษาปริทรรศน์ มจร, 2016)
This article aimed to present resilience quotient (RQ) which was regarded as emotional and mental potentials individuals should learn and adapt when confronting with difficult situations. People who gained this ability can bounce back from the negative experience to the normal functioning after adversity. Resilience is considered to be mental power which prevent and nurture one facing the unexpected or uncontrollable hardship. Moreover, resilient people can also overcome those critical crisis which may lead to mental illness. Moreover this paper describe the significance of RQ and how to enhance RQ in order to balance negative emotions with positive ones, by adapting thought, emotion, behavior and goal-setting. Therefore resilient individuals have optimistic attitude and positive emotion, so they can live happily in the world of rapid changes.